2007
DOI: 10.7205/milmed.172.2.182
|View full text |Cite
|
Sign up to set email alerts
|

High-Intensity Acoustics for Military Nonlethal Applications: A Lack of Useful Systems

Abstract: There have been many previous claims of nonlethal acoustic weapon effects, mostly in the popular rather than the scientific literature. Anecdotal reports of extraordinary effects can make meaningful assessment and review of this area very difficult. Acoustics research has shown that the nonlethal weapon capabilities of audible sound generators have been grossly overstated. Although high-intensity infrasound significantly disrupted animal behavior in some experiments, the generation of such energy in a volume l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Although infrasound at high levels apparently does not cause direct mechanical damage to the ear (Westin 1975, Jauchem and Cook, 2007) in animal studies it has been found to exacerbate functional and hair cell losses resulting from high level exposures of sounds in the audible range (Harding et al, 2007). This was explained as possibly resulting from increased mixture of endolymph and perilymph around noise induced lesion sites in the presence of infrasound.…”
Section: Physiologic Responses Of the Ear To Low Frequency Stimulimentioning
confidence: 99%
“…Although infrasound at high levels apparently does not cause direct mechanical damage to the ear (Westin 1975, Jauchem and Cook, 2007) in animal studies it has been found to exacerbate functional and hair cell losses resulting from high level exposures of sounds in the audible range (Harding et al, 2007). This was explained as possibly resulting from increased mixture of endolymph and perilymph around noise induced lesion sites in the presence of infrasound.…”
Section: Physiologic Responses Of the Ear To Low Frequency Stimulimentioning
confidence: 99%
“…At audio frequencies, confinement has received most attention, with recent success despite a poor initial record [157]. There has been considerable publicity given to non-lethal sonic weapons for crowd control, marine vessel protection etc.…”
Section: (4) Ultrasonic Weaponsmentioning
confidence: 99%
“…Furthermore, the state of sonic weaponry is crude and impractical due to physical limitations such as the size of the device required and the laws of physics. 8 Some police agencies use long-range acoustic devices to disperse crowds of protestors, but there is nothing subtle or mysterious about them. They are nicknamed ‘sound cannons’ due to their capacity to generate loud noises.…”
Section: A Crime In Search Of a Perpetratormentioning
confidence: 99%